Development of an Outdoor Play-Based Learning Model to Train Gross Motor Skills in Early Childhood - muhammad nasihul waffak; Ervin Arifianti; Rini Agustiningsih (UNIB Press, 2024)
Study objectives Researchers realize that children's motoric learning is often neglected or forgotten by parents, mentors or even teachers themselves because the orientation is still in the cognitive aspect andTeachers do not yet understand that the development of motor learning is an inseparable part of children's lives. This research aims to identify the development of gross motor skills in early childhood using an outdoor play approach. Procedure: This research uses a quantitative approach in testing the validity of the content as well as the construct and effectiveness of the educational model. The experimental subjects in this research were early childhood children, totaling 26 respondents in Yogyakarta, Indonesia. Data analysis for small scale trials and large scale trials uses path analysis of the reliability coefficient categories. The paired illustrative t test was used to analyze the effectiveness of developing gross motor skills. Results: The results of this research are an educational model that uses an outdoor play approach to improve aggressive motor skills in the form of a novel guide. Conclusion. The model developed in this research can train gross motor skills and will influence the cognitive, affective and psychomotor learning outcomes of early childhood students. So the learning model is easy to understand, comfortable, and makes early childhood students more enthusiastic about studying.